Experimental selection of long-term intracellular mycobacteria - Vázquez, Cristina L (Cell Microbiol, 2014)
Some intracellular bacteria are known to cause long-term infections that last decades without compromising the viability of the host. Although of critical importance, the adaptations that intracellular bacteria undergo during this long process of residence in a host cell environment remain obscure. Here, we report a novel experimental approach to study the adaptations of mycobacteria imposed by a long-term intracellular lifestyle. Selected Mycobacterium bovis BCG through continuous culture in macrophages underwent an adaptation process leading to impaired phenolic glycolipids (PGL) synthesis, improved usage of glucose as a carbon source and accumulation of neutral lipids. These changes correlated with increased survival of mycobacteria in macrophages and mice during re-infection and also with the specific expression of stress- and survival-related genes. Our findings identify bacterial traits implicated in the establishment of long-term cellular infections and represent a tool for understanding the physiological states and the environment that bacteria face living in fluctuating intracellular environments.